Anorectal malformation in a 46,XY patient with a de novo stop-loss variant in PPP1R12A and associated difference in sexual development: A case report - Kelly T. Harris; Daniel G. Pique; Lea A. Wehrli; Andrew Trecartin; Jonathan Roach; Naomi J. Meeks; Natalie J. Nokoff; Duncan T. Wilcox; Andrea Bischoff (Elsevier, 2023)
Introduction: Here we report an infant with a 46,XY karyotype and novel de novo PPP1R12A stop-loss variant with a concomitant anorectal malformation (ARM) and difference in sex development (DSD). Case report: This is an infant born with ambiguous genitalia and rectoperineal fistula. Genetic testing confirmed a 46,XY chromosomal complement and whole exome sequencing demonstrated a novel de novo heterozygous PPP1R12A stop-loss variant. The infant underwent tapering jejunoplasty, proximal jejunostomy and mucous fistula creation for jejunal atresia and posterior sagittal anorectoplasty for the ARM. The gonad will be addressed with a biopsy and orchiopexy when the infant reaches six months of age. Conclusion: Although Müllerian anomalies and hypospadias may be common with ARM, a true DSD of this nature is exceedingly rare. Multidisciplinary care with urology, endocrinology, genetics, and colorectal surgery is paramount to providing optimal care for this patient.